An evaluation of oral dabigatran etexilate pharmacokinetics and pharmacodynamics in hemodialysis. (28th May 2014) - Wilson, Jo‐Anne S.; Goralski, Kerry B.; Soroka, Steven D.; Morrison, Matthew; Mossop, Paula; Sleno, Lekha; Wang, Yan; Anderson, David R.
Abstract Dabigatran etexilate represents a possible improved alternative to warfarin for anticoagulation in hemodialysis patients with atrial fibrillation (AF). The objective was to determine dabigatran plasma concentrations and anticoagulant effects following administration of a single 110 mg oral dose of dabigatran etexilate to 10 adult patients immediately prior to starting hemodialysis. Mass spectrometry and the Hemoclot® assay were used, respectively, to determine free (unconjugated) dabigatran concentrations and thrombin time (TT) in plasma samples collected intermittently over 48 hours. The median time (tmax) to reach the maximum plasma‐free dabigatran concentration (Cmax) was 2 hours (range 1–3 hours). The mean free dabigatran Cmax was 95.5 ± 33.4 ng/mL. The mean elimination half‐lives on and off hemodialysis were, respectively, 2.6 ± 1.3 and 30.2 ± 7.8 hours. Hemodialysis effectively removed dabigatran with an extraction ratio of 0.63 ± 0.07. The maximal TT ratio was 2.1 and the TT ratio demonstrated a strong linear dependence on free dabigatran concentration (r2 = 0.741). A 110 mg oral dabigatran dose prior to hemodialysis was rapidly absorbed and achieved therapeutic concentrations. Hemodialysis effectively removed dabigatran from the plasma and may be an effective means of accelerating the elimination of dabigatran in circumstances of excessive anticoagulation.